A relação sujeito-língua: marcas de heterogeneidade nos dizeres de professores nativos de Português Língua Estrangeira - Isis Del Grego Herrmann , Ingrid (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
The current article aims at presenting an analysis of the relation between subject and foreign language, having as its focus Portuguese as a Foreign Language teachers and the heterogeneity elements which arise from their words. This study comes from considerations developed in my Master‟s dissertation (HERRMANN, 2012), in which representations of language, teacher and student for those teachers are analysed. The main question lies on the argument that, according to a discursive perspective, (ORLANDI, 2002; CORACINI, 2007, BERTOLDO, 2003), being a native speaker of a language does not guarantee the gesture of being its teacher and the - 10 - Revista Multidisciplinar Acadêmica Vozes dos Vales – UFVJM – MG – Brasil – Nº 04 – Ano II – 10/2013 Reg.: 120.2.095–2011 – UFVJM – QUALIS/CAPES – LATINDEX – ISSN: 2238-6424 – www.ufvjm.edu.br/vozes language one teaches does not seem to be the same they learned, for, in such language, there is a constitution of different representations about language, teaching and others, and these may lead to the eruption of heterogeneity elements in their words.